STIM2 Contributes to Enhanced Store‐Operated Ca 2+ Entry in Pulmonary Artery Smooth Muscle Cells from Patients with Idiopathic Pulmonary Arterial Hypertension - Song, Michael Y.; Makino, Ayako; Yuan, Jason X.‐J. (Pulmonary circulation, 2011)
Pulmonary vasoconstriction and vascular remodeling are two major causes for elevated pulmonary vascular resistance and pulmonary arterial pressure in patients with idiopathic pulmonary arterial hypertension (IPAH). An increase in cytosolic free Ca 2+ concentration ([Ca 2+ ] cyt ) in pulmonary artery smooth muscle cells (PASMC) is a major trigger for pulmonary vasoconstriction and an important stimulus for PASMC proliferation, which causes pulmonary vascular remodeling. Store‐operated Ca 2+ entry (SOCE), induced by depletion of stored Ca 2+ in the sarcoplasmic reticulum (SR), can increase [Ca 2+ ] cyt in PASMC, independent of other means of Ca 2+ entry. Stromal interaction molecule (STIM) proteins, STIM1 and STIM2, were both recently identified as sensors for store depletion and also signaling molecules to open store‐operated Ca 2+ channels. We previously reported that SOCE was significantly enhanced in PASMC from IPAH patients compared to PASMC from normotensive control subjects. Enhanced SOCE plays an important role in the pathophysiological changes in PASMC associated with pulmonary arterial hypertension. In this study, we examine whether the expression levels of STIM1 and STIM2 are altered in IPAH‐PASMC compared to control PASMC, and whether these putative changes in the STIM1 and STIM2 expression levels are responsible for enhanced SOCE and proliferation in IPAH‐PASMC. Compared to control PASMC, the protein expression level of STIM2 was significantly increased in IPAH‐PASMC, whereas STIM1 protein expression was not significantly changed. In IPAH‐PASMC, the small interfering RNA (siRNA)‐mediated knockdown of STIM2 decreased SOCE and proliferation, while knockdown of STIM2 in control PASMC had no effect on either SOCE or proliferation. Overexpression of STIM2 in the control PASMC failed to enhance SOCE or proliferation. These data indicate that enhanced protein expression of STIM2 is necessary, but not sufficient, for enhanced SOCE and proliferation of IPAH‐PASMC.